Técnicas de estudio colaborativo y su impacto en el rendimiento académico de los estudiantes de básica media de la Unidad Educativa Mateo Celestino Espinoza del cantón Naranjito periodo lectivo 2024-2025 - Gutierrez Mosquera, Angie Lissette (2025)
This research analyzes the impact of collaborative study techniques on the academic performance of secondary school students at the Mateo Celestino Espinoza Educational Unit in the Naranjito canton during the 2024-2025 school year. The study used a mixed methodology, combining quantitative and qualitative approaches, with a sample of 60 students and 2 teachers. Surveys, interviews, and direct observation were applied to collect data on the implementation and effectiveness of collaborative techniques. The results revealed that 75% of students reported a better understanding of the content through group work, while 80% showed greater motivation for learning. Grades improved in 72% of cases according to the students' perception. It was also observed that 79% of participants positively valued the assignment of roles in group work, and 75% reported improvements in the development of critical thinking through the exchange of ideas. Teachers confirmed that they observed significant improvements in participation, communication and understanding of content. The strategies implemented included project-based learning, the puzzle method and group discussions. However, challenges were identified such as conflict management, uneven participation in groups and the initial resistance of some students to collaborative work. The research concludes that collaborative study techniques have a positive impact on academic performance when properly implemented, not only in terms of grades but also in the development of social skills and problem solving.